Misapproriation Asset On Public Sector; Diamond Fraud Theory - Ibrahim, Erni Cahyani (Universitas Islam Negeri Alauddin Makassar, 2023)
Asset misappropriation is not only found in the private sector, but it can occur in the public sector. This study aims to analyze how much influence the concept of fraud diamond theory has on government employees as individuals who have the authority to carry out their main duties and functions to improve institutional performance, but on the other hand have an interest in always ensuring their welfare. The data analysis method uses multiple linear regression techniques. The results of the study show that pressure and capability have a positive and significant effect on asset misappropriation in the public sector, while opportunity and rationalization have no effect. Focusing on efforts to prevent misappropriation of assets is important for the government to pay attention to by ensuring employee welfare is met according to their rights.